The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/bf02512230
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning and pragmatics

Abstract: pragmatics, reasoning, deduction, conditional reasoning, judgment, probabilistic reasoning,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…A broad paradigm of taking semantic and pragmatic factors into account when analysing reasoning behaviour has been advocated by Stenning and van Lambalgen (2001. Recently, Politzer (2004) (and see also Politzer and Macchi 2002) has lain out arguments for the necessity of both a macroanalysis and a microanalysis of the semantic structure of experimental tasks. The latter term is Politzer's label for precisely what we hope to achieve in the current study: based on pragmatic theory, the aim of the microanalysis is to output "the determination of the interpretation of the premises, conclusion or question which the participant is likely to work out."…”
Section: Premises In Everyday Languagementioning
confidence: 99%
“…A broad paradigm of taking semantic and pragmatic factors into account when analysing reasoning behaviour has been advocated by Stenning and van Lambalgen (2001. Recently, Politzer (2004) (and see also Politzer and Macchi 2002) has lain out arguments for the necessity of both a macroanalysis and a microanalysis of the semantic structure of experimental tasks. The latter term is Politzer's label for precisely what we hope to achieve in the current study: based on pragmatic theory, the aim of the microanalysis is to output "the determination of the interpretation of the premises, conclusion or question which the participant is likely to work out."…”
Section: Premises In Everyday Languagementioning
confidence: 99%
“…The exchange between subject and predicate is likely to suggest a change in topic (as opposed to focus): Asserting some Q are P instead of some P are Q may definitely alter the point of an argument so that participants (even among those who are aware of their logical equivalence) may be reluctant to accept the inference of I to I′ and E to E′. Participants who represent the task as an inquiry about common sense reasoning (rather than about formal logic) are likely to be sensitive to such pragmatic determinants of sentence comprehension (Politzer, 1997(Politzer, , 2004aPolitzer & Macchi, 2000). In summary, the inference task requires more processing than just a semantic appreciation of the quantified sentences; the task often allows for a range of interpretations.…”
Section: To What Extent Is the Inference Task Relevant?mentioning
confidence: 99%
“…It is clear that a judgment can be deemed to have been made in accordance with some principle only to the extent that the interpretation of the problem statement and of the question made by the participant and the experimenter coincide. This approach to the experimental study of thinking and reasoning, often called "conversational approach", has been suggested or applied by a number of researchers (Adler 1991, Hilton 1995, Macchi 2000, Politzer 1986and 1991, Politzer and Macchi 2000, Schwarz 1996. It is quite general and can change our understanding of some tasks radically (see Sperber et al 1995 for Wason's selection task).…”
mentioning
confidence: 99%